Moral hazard and bail-out in fiscal federations: evidence for the German Länder - Kirsten H. Heppke-Falk; Guntram B. Wolff (Deutsche Bundesbank, 2007)
We identify investor moral hazard in the German fiscal federation. Our identification strategy is based on a variable, which was used by the German Federal Constitutional Court as an indicator to determine eligibility of two German states (Länder) to a bail-out, the interest payments-to-revenue ratio. While risk premia measured in the German sub-national bond market react significantly to the relative debt level of a state (Land), we also find that a larger interest payments-to-revenue ratio counter-intuitively lowers risk premia significantly. Furthermore, with increasing values the risk premia decrease more strongly. This is evidence of investor moral hazard, because a larger indicator value increases the likelihood of receiving a bail-out payment. Quantitatively, the effects are, however, quite small. Our findings are robust to a variety of sample changes. In addition, we provide a case study of the recent Federal Constitutional Court ruling on the Land Berlin, which had filed for additional federal funds. The negative response of the court did not lead to a change in financial markets' bail-out expectations. In sum, our results indicate significant investor moral hazard in the sub-national German bond market.
Keywords: F34; H6; H7; G14; G15; E62; 330; moral hazard; bail-out; sovereign bond spreads; fiscal federalism; Germany; Länderfinanzen; Öffentliche Schulden; Öffentliche Anleihe; Risikoprämie; Finanzausgleich; Moral Hazard; Schätzung; Deutschland; Berlin